Prevalence of post-traumatic stress disorder and associated factors among police officers in Central Gondar Zone, North West Ethiopia, 2023: institutional-based cross-sectional study - Adugna, Biruk; Tesfaye, Bizuneh; Ali, Dawed; Mirkena, Yohannes; Getinet, Wondale (Frontiers in Psychiatry, 2024)
Background: Post-traumatic stress disorder (PTSD) is a psychiatric disorder that follows exposure to a traumatic or stressful life event. Police officers are exposed to a number of traumatic events that put them at risk of developing post-traumatic stress disorder. Previous studies have found the prevalence of post-traumatic stress disorder among police officers to be varied and inclusive. However, in Ethiopia, little is known about the prevalence of posttraumatic stress disorder and associated factors among police officers. Therefore, assessing the prevalence and associated factors of post-traumatic stress disorder among police officers might have a plausible role in future investigations.The aim of this study was to assess the prevalence of post-traumatic stress disorder and associated factors among police officers in Central Gondar Zone, North West Ethiopia, 2023.Methods: An institutional-based cross-sectional study was conducted in central Gondar zone by using self-administered and semi-structured questionnaires. A multi-stage cluster sampling technique was employed to select a sample of 634 participants. Post-traumatic stress disorder was assessed using the PTSD Checklist DSM-5. The collected data were coded and entered using Epi data Software version 4.6.02 and then exported to STATA version 14 for analysis.Bivariable and multivariable logistic regression analyses were done to identify factors associated with post-traumatic stress disorder. Statistically significant results were declared at a 95% confidence interval (CI) of a p-value less than 0.05.The prevalence of post-traumatic stress disorder was found to be 15.2%, with a 95% CI of 12.5 to 18.3%. In the multivariate analysis, Female (AOR=3.36, 95% CI 1.95, 5.78), being directly exposed to traumatic events (AOR=2.01, 95% CI 1.16, 3.48), current alcohol use (AOR=2.90, 95% CI 1.65, 5.12), and having poor social support (AOR=4.25, 95% CI 1.58, 11.36) were factors significantly associated with post-traumatic stress disorder.Conclusions: According to this study, police officers suffered from a significant burden of post-traumatic stress disorder. Female, police personnel directly exposed to traumatic events, current alcohol users, and those who had poor social support were found to be strongly associated with post-traumatic stress disorder. Therefore, early detection and intervention are crucial to mitigating the overall problem.